Letter to the Editorial Office: Global Ballistic Missile Defense and Strategy of Zero Growth vs. Necessity of Global Cooperation for Sustainable Development - Michnowski, Lesław (Problemy Ekorozwoju, 2009)
The problem of building the American defense system missile defense needs to be looked at in perspective global crisis and the type of correct defensive strategy to overcome it.